2019
DOI: 10.1016/j.ntt.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Paternal nicotine exposure in rats produces long-lasting neurobehavioral effects in the offspring

Abstract: Studies of intergenerational effects of parental chemical exposure have principally focused on maternal exposure, particularly for studies of adverse neurobehavioral consequences on the offspring. Maternal nicotine exposure has long been known to cause adverse neurobehavioral effects on the offspring. However, paternal toxicant exposure has also been found to cause neurobehavioral toxicity in their offspring. Recent work suggests that paternal nicotine exposure can have epigenetic effects, although it remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…While we were able to characterize these changes in the sperm of exposed rats, we have not yet examined potential heritability of these changes. Initial studies have demonstrated behavioral effects as the result of paternal exposure to nicotine 67 and THC 68 . It will be important to examine offspring brain DNA methylation and relationship to behavioral effects.…”
Section: Discussionmentioning
confidence: 99%
“…While we were able to characterize these changes in the sperm of exposed rats, we have not yet examined potential heritability of these changes. Initial studies have demonstrated behavioral effects as the result of paternal exposure to nicotine 67 and THC 68 . It will be important to examine offspring brain DNA methylation and relationship to behavioral effects.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dams were exposed only to e-cigarette aerosol after the presence of a seminal plug, with no exposures occurring prior to the start of pregnancy. A previous study in rats noted a developmental impact on offspring following daily paternal nicotine injections (2 mg=kg) to the males prior to the start of breeding (Hawkey et al 2019). Therefore, e-cigarette aerosols with and without nicotine may have additive or synergistic effects when exposure occurs prior to pregnancy and during the gestational period and when both biological parents are exposed.…”
Section: Comparison With Human E-cigarette Use and Study Limitationsmentioning
confidence: 99%
“…We next sought to determine whether paternal CS exposure had any effect on offspring phenotype. Given that brain and nervous systems were previously reported to be sensitive to preconception paternal exposures [25][26][27][28], we investigated DNAme by RRBS in the prefrontal cortex of F1 mice derived from CS-exposed sires compared to the offspring of unexposed males (n = 8 per group). These experiments were performed exclusively on male mice in order to avoid confounding due to sex-related differences in DNA methylation and RNA expression.…”
Section: Paternal Cs Exposure Impacted Dname and Gene Expression Chanmentioning
confidence: 99%
“…The findings reported here may also be useful in understanding the risks of other environmental exposures that induce oxidative stress such as air pollution and some chemical exposures. Paternal preconception exposures to a variety of pharmacologic agents and pollutants, including nicotine, THC, morphine, and benzo[a]pyrene affect offspring phenotype, and often confer neurobehavioral consequences [25][26][27][28][51][52][53][54]. In some cases, the impacts are transmitted across multiple generations [52,53].…”
Section: Prefrontal Cortex Gene Expression Variation and Correlation mentioning
confidence: 99%